Berpastoral Dalam Budaya Mamuleng Wale Suku Tonsea - Lumunder, Epafras Mario; Pantouw, Frilly Omega; Kondoy, Monalisa; Manorek, Indah Terok Elfatah; Oley, Deby Meilina (PADAMARA: Jurnal Psikologi dan Sosial Budaya, 2024)
Mapalus is a reflection of the morality of mutual cooperation in Minahasa, which involves cooperation in various aspects of life, especially in agriculture, house construction, and other social activities. This culture has been passed down from generation to generation and has become an integral part of the life of the Minahasa people. The method applied in this research is qualitative. This research uses a qualitative method with a descriptive approach, which aims to describe various theories related to the content and needs of the research. The values of togetherness, helping, and solidarity contained in Mapalus and Mamuleng Wale continue to be valued and practiced in various aspects of social life, including in village development and church activities. Pastoral assistance that is integrated in the practice of